Optimalisasi Layanan Bimbingan dan Konseling dalam Meningkatkan Kesejahteraan Psikologis Peserta Didik mtsn - 220102110033, fahmi fedora (Maliki Interdisciplinary Journal, 2025)
Guidance and Counseling (BK) services in madrasahs have an important role in developing students' potential optimally, both in terms of personal, social, learning, and career aspects. This article aims to describe the strategy for optimizing BK services in the State Junior High School (MTsN) in improving students' psychological well-being. The methods used are literature study and participatory observation in MTsN 4 Blitar. The results of the study indicate that structured BK services, based on a humanistic and Islamic approach, and integrated with school activities as a whole, are able to improve students' emotional well-being, positive social relationships, and learning motivation. This article recommends strengthening the role of BK teachers through collaboration between parties, increasing professional capacity, and utilizing digital media in counseling services.